Thermal Decoupling May Promote Cooling and Avoid Heat Stress in Alpine Plants - Loreto V. Morales; Angela Sierra-Almeida; Catalina Sandoval-Urzúa; Mary T. K. Arroyo (Plants, 2025)
In alpine ecosystems, where low temperatures predominate, prostrate growth forms play a crucial role in thermal resistance by enabling thermal decoupling from ambient conditions, thereby creating a warmer microclimate. However, this strategy may be maladaptive during frequent heatwaves driven by climate change. This study combined microclimatic and plant characterization, infrared thermal imaging, and leaf photoinactivation to evaluate how thermal decoupling (TD) affects heat resistance (LT50) in six alpine species from the Nevados de Chillán volcano complex in the Andes of south-central Chile. Results showed that plants’ temperatures increased with solar radiation, air, and soil temperatures, but decreased with increasing humidity. Most species exhibited negative TD, remaining 6.7 K cooler than the air temperature, with variation across species, time of day, and growth form; shorter, rounded plants showed stronger negative TD. Notably, despite negative TD, all species exhibited high heat resistance (Mean LT50 = 46 °C), with LT50 positively correlated with TD in shrubs. These findings highlight the intricate relationships between thermal decoupling, environmental factors, and plant traits in shaping heat resistance. This study provides insights into how alpine plants may respond to the increasing heat stress associated with climate change, emphasizing the adaptive significance of thermal decoupling in these environments.